MAGNETIC NANOSTRUCTURES : FABRICATION AND APPLICATIONS FROM MEMORY DEVICES TO BIOSENSOR - E. Suharyadi; E A Setiadi; A Riyanto; T Kato; S Iwata; K Abraha (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2014)
MAGNETIC NANOSTRUCTURES : FABRICATION AND APPLICATIONS FROM MEMORY DEVICES TO BIOSENSOR. For magnetic storage application, we successfully fabricated nanodots and nanopattern using electron-beam lithography (EBL) technique followed by ion irradiation. Perpendicularly magnetized squared-bits with the sizes of 100 to 500 nmwere clearly observed using magnetic forcemicroscopy (MFM) images. MFM images showed that the most of the patterned squared-bits with size of 100 nm have either uniformly bright or dark magnetic contrasts. Magnetization curves of patterned films were strongly influenced by the bit size and spacing between bits and indicated the existence of exchange coupling between the bits via irradiated spacing. On the other hand, for biosensor application, we recently develop Surface Plasmon Resonance (SPR)-based biosensor for biomolecules detection device.Magnetic nanoparticles such as magnetite (Fe3O4) and CoFe2O4 were purposed as candidate for active materials to increase accumulation of target biomolecules on sensing surface of SPR-based biosensor. Fe3O4 and CoFe2O4 nanoparticles with different sizes of 8 to 17 nm have been successfully synthesized chemically by co-precipitation method. The surface of nanoparticles had been modified using polyethylene glycol (PEG)-4000 to increase the crystallinity, decrease agglomeration and control the shape to more spherical. However, modification using PEG-4000 decreased the saturation magnetization which is due to the existence of α-FeO(OH) and γ-FeO(OH) phases from bonds at interface of CoFe2O4.